Activation of Transition Metal (Fe, Co and Ni)-Oxide Nanoclusters by Nitrogen Defects in Carbon Nanotube for Selective CO2 Reduction Reaction - Cheng, Yi; Chen, J.; Yang, C.; Wang, H.; Johannessen, B.; Thomsen, L.; Saunders, M.; Xiao, J.; Yang, S.; Jiang, San Ping (WILEY, 2023)
The electrochemical carbon dioxide reduction reaction (CO2RR), which can produce value-added chemical feedstocks, is a proton-coupled-electron process with sluggish kinetics. Thus, highly efficient, cheap catalysts are urgently required. Transition metal oxides such as CoOx, FeOx, and NiOx are low-cost, low toxicity, and abundant materials for a wide range of electrochemical reactions, but are almost inert for CO2RR. Here, we report for the first time that nitrogen doped carbon nanotubes (N-CNT) have a surprising activation effect on the activity and selectivity of transition metal-oxide (MOx where M = Fe, Ni, and Co) nanoclusters for CO2RR. MOx supported on N-CNT, MOx/N-CNT, achieves a CO yield of 2.6–2.8 mmol cm−2 min−1 at an overpotential of −0.55 V, which is two orders of magnitude higher than MOx supported on acid treated CNTs (MOx/O-CNT) and four times higher than pristine N-CNT. The faraday efficiency for electrochemical CO2-to-CO conversion is as high as 90.3% at overpotential of 0.44 V. Both in-situ XAS measurements and DFT calculations disclose that MOx nanoclusters can be hydrated in CO2 saturated KHCO3, and the N defects of N-CNT effectively stabilize these metal hydroxyl species under carbon dioxide reduction reaction conditions, which can split the water molecules and provide local protons to inhibit the poisoning of active sites under carbon dioxide reduction reaction conditions.